2010
DOI: 10.1162/jocn.2008.21170
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring in Language Perception: Mild and Strong Conflicts Elicit Different ERP Patterns

Abstract: In the language domain, most studies of error monitoring have been devoted to language production. However, in language perception, errors are made as well and we are able to detect them. According to the monitoring theory of language perception, a strong conflict between what is expected and what is observed triggers reanalysis to check for possible perceptual errors, a process reflected by the P600. This is at variance with the dominant view that the P600 reflects syntactic reanalysis or repair, after syntac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
142
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 53 publications
8
142
2
1
Order By: Relevance
“…Therefore, the Semantic Attraction account cannot explain the P600-effect for the sentences of van Herten et al (2005). van Herten et al (2005van Herten et al ( , 2006 offered an explanation for the presence of an SIE in terms of a framework called Monitoring Theory (see also Kolk and Chwilla, 2007;Kolk et al, 2003;van de Meerendonk et al, 2009van de Meerendonk et al, , 2010Vissers et al, 2007;Ye and Zhou, 2008). They proposed an architecture in which an algorithmic, syntax-driven stream works in parallel to a plausibility heuristic driven by world knowledge.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the Semantic Attraction account cannot explain the P600-effect for the sentences of van Herten et al (2005). van Herten et al (2005van Herten et al ( , 2006 offered an explanation for the presence of an SIE in terms of a framework called Monitoring Theory (see also Kolk and Chwilla, 2007;Kolk et al, 2003;van de Meerendonk et al, 2009van de Meerendonk et al, , 2010Vissers et al, 2007;Ye and Zhou, 2008). They proposed an architecture in which an algorithmic, syntax-driven stream works in parallel to a plausibility heuristic driven by world knowledge.…”
Section: 1mentioning
confidence: 99%
“…A number of studies (Hoeks et al, 2004;van de Meerendonk et al, 2010;van Herten et al, 2006;van Petten and Luka, 2006; for an overview, see van Petten and Luka, in press) have shown that some sentences engender biphasic N400/P600-effects and not only an N400-effect (for implausibility), or only a P600-effect (for conflicting streams). Hoeks et al (2004), for instance, observed such a biphasic pattern in response to 'De speer heeft de atleten opgesomd' (lit: The javelin has the athletes summarized) relative to 'De speer werd door de atleten geworpen' (lit: The javelin was by the athletes thrown).…”
Section: Monitoring Theorymentioning
confidence: 99%
“…Many have shown that comprehenders can readily detect the implausibility that results from the reversal of the arguments' roles (e.g., Kolk et al, 2003). Further, ERP studies across different languages have shown that argument role reversals elicit a larger late positivity (a P600 effect; e.g., Kim & Osterhout, 2005;Kolk et al, 2003;Stroud & Phillips, 2012;Ye & Zhou, 2008), which has been associated with error detection and reanalysis (Coulson, King, & Kutas, 1998;Hagoort, Brown, & Groothusen, 1993;Hahne & Friederici, 1999;Kuperberg, 2007;Osterhout & Holcomb, 1992;van de Meerendonk, Kolk, Vissers, & Chwilla, 2010). These results suggest that information about the arguments' structural roles can immediately impact comprehenders' interpretation, but it does not seem to affect the cognitive processes that underlie the N400 response.…”
Section: Prediction In the Processing Of Thematic Relationsmentioning
confidence: 99%
“…The second factor, conflict strength, has been manipulated in some studies based on the idea that for reasons of efficiency only representational conflicts that are sufficiently strong (i.e., pass a certain 'threshold') should trigger reprocessing of the input. For example, Van de Meerendonk et al (2010) induced differences in conflict strength by varying plausibility. In the sentence context the critical words could either be plausible, mildly implausible, or deeply implausible.…”
Section: General Introductionmentioning
confidence: 99%
“…The hypothesis that the P600 effect reflects a more general reanalysis has been strengthened by a number of recent studies (for reviews on these studies see Kolk and Chwilla, 2007;Kuperberg, 2007;Van de Meerendonk et al, 2009), demonstrating P600 effects to different kinds of semantic anomalies (e.g., Ganushchak and Schiller, 2010;Hoeks et al, 2004;Kim and Osterhout, 2005;Kolk et al, 2003;Kuperberg et al, 2006Kuperberg et al, , 2007Kuperberg et al, , 2003b; Van de Meerendonk et al, 2010;Van Herten et al, 2006, 2005. Furthermore, P600 effects were found to picture-sentence mismatches in which the sentences violated the semantics of a previously shown picture (Vissers et al, 2008).…”
mentioning
confidence: 99%